47th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2009
DOI: 10.2514/6.2009-1315
|View full text |Cite
|
Sign up to set email alerts
|

Hypersonic Flow Over a Flat Plate: CFD Comparison with Experiment

Abstract: Experimental results of a hypersonic flow over a flat plate are compared with a CFD simulation. Slip boundary conditions are employed in the CFD simulation, with the accommodation coefficient being varied between 0.5 and 1.0. Detailed velocity profiles in both the x-and y-directions are compared with the experimental data, as well as slip velocity at the wall. A brief comparison is also made to similar simulation results using DSMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…These results also agree qualitatively with trends observed computational fluid dynamics simulations [37] and measurements [38] of hypersonic flow over a flat plate. The results showed that the skin friction and boundary-layer thickness decreased as the momentum accommodation coefficient decreased, which corresponds to an increase in K.…”
Section: Fluid Flow Resultssupporting
confidence: 89%
“…These results also agree qualitatively with trends observed computational fluid dynamics simulations [37] and measurements [38] of hypersonic flow over a flat plate. The results showed that the skin friction and boundary-layer thickness decreased as the momentum accommodation coefficient decreased, which corresponds to an increase in K.…”
Section: Fluid Flow Resultssupporting
confidence: 89%
“…This calculation does a better job at matching experimental normal stress and suggests that the accommodation coefficient in experiments varied spatially. Similar trends were noted by Lofthouse and Boyd [13]. These are discussed in Sec.…”
Section: B Uncertainties In the Surface Fluxessupporting
confidence: 85%
“…The uncertainty in the accommodation coefficient is expected to be large because the coefficient depends on surface properties, surface finish, temperature, chemistry, and molecular gas properties that are difficult to measure experimentally and may change in flight. By comparing their numerical simulations of Mach 11.9 nitrogen flow above a flat plate to Cecil and McDaniel's experiments [12], Lofthouse and Boyd [13] showed that, near a LE, an accommodation coefficient of 0.5 reproduces the experimental slip velocities accurately but an accommodation coefficient of 0.75 provides a better match 12.5 mm from the LE. On the other hand, the accommodation coefficient should be decreased in the downstream direction to best reproduce the normal velocity components.…”
Section: Introductionmentioning
confidence: 98%
“…For example, the tangential and energy accommodation factors affect the CFD solutions. Tangential accommodation values of 0.5 seem to provide accurate results near the leading edge, whereas values between 0.75 and 1.0 yield the best agreement further along the plate [6]. The same author in another publication [7] claimed that the difficulty of defining these slip conditions is in determining the correct values for the coefficients mentioned above and other empirical terms required for the implementation.…”
Section: Recent Trends In Computational Science and Engineeringmentioning
confidence: 99%
“…Consider the Integro-Differential Model (IDM) as it is applied to the computational solution to the NSE (1)(2)(3)(4)(5)(6)(7)(8). In general, the IDS solution of a given fluid dynamic problem is built on an interconnecting set of spatial and temporal fluid cells.…”
Section: The Ids Fluid Modelmentioning
confidence: 99%